2010
DOI: 10.1590/s1516-44462010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders among medical students at Universidade Federal de Sergipe: a cross-sectional study

Abstract: Objective: Estimate the prevalence of common mental disorder and its associated factors among medical students of the Universidade Federal de Sergipe. Method: A cross-sectional study was carried out, applying Self Reporting Questionnaire-20 to 473 students from the 512 medical students enrolled in 2006 and compared with compared with a structured questionnaire by the authors containing information on the socio-demographic characteristics, the teaching-learning process and the psycho-emotional experiences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 22 publications
3
27
3
23
Order By: Relevance
“…13,15,19 CMD prevalence among the students at the beginning of their program was low and similar to that observed in the general population. This finding was expected because the students answered the questionnaire on the first day of school.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…13,15,19 CMD prevalence among the students at the beginning of their program was low and similar to that observed in the general population. This finding was expected because the students answered the questionnaire on the first day of school.…”
Section: Discussionsupporting
confidence: 73%
“…In our study, an increased prevalence of CMD is noted in our institution during the fifth program year (semester 9); this period corresponds to the transition to the internship, which begins in the tenth semester. 13,24 We consider that the CMD prevalence falls in the 6 th program year, maybe due to overcoming the internship transition stress as well as to the greater integration of knowledge acquired over the years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 At the same university, a recent study including only medical students revealed a high prevalence of common mental disorder (42.5%). 14 To date, in this institution, there are no published researches on the mental health of nursing and dental students. National and international studies assessing this kind of population are also scarce.…”
Section: Introductionmentioning
confidence: 99%